2007
DOI: 10.1007/s00284-007-9033-4
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Chitinases from Trichoderma aureoviride DY-59 and Rhizopus microsporus VS-9

Abstract: Two chitinolytic fungal strains, Trichoderma aureoviride DY-59 and Rhizopus microsporus VS-9, were isolated from soil samples of Korea and Vietnam, respectively. DY-59 and VS-9 crude chitinases secreted by these fungi in the 0.5% swollen chitin culture medium had an optimal pH of 4 and the optimal temperatures of 40 degrees C and 60 degrees C, respectively. Enzymatic hydrolysis products from crab swollen chitin were N-acetyl-beta-D-glucosamine (GlcNAc) by DY-59 chitinase, and GlcNAc and N, N'-diacetylchitobios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…The antifungal activity exhibited a close relationship with production of chitinase and siderophores (Cazorla et al , ; Pliego et al , ). Chitinolytic enzymes have been studied as potential antifungal agents against chitin‐bearing plant pathogens because the enzymes play a key role in the mechanism of parasitic entry into host cells (Nguyen et al , ). Siderophores bind to the available form of iron (Fe 3+ ) in the rhizosphere, thus making it unavailable to the phytopathogens and protecting the plant health (Ramos‐Solano et al , ).…”
Section: Discussionsupporting
confidence: 90%
“…The antifungal activity exhibited a close relationship with production of chitinase and siderophores (Cazorla et al , ; Pliego et al , ). Chitinolytic enzymes have been studied as potential antifungal agents against chitin‐bearing plant pathogens because the enzymes play a key role in the mechanism of parasitic entry into host cells (Nguyen et al , ). Siderophores bind to the available form of iron (Fe 3+ ) in the rhizosphere, thus making it unavailable to the phytopathogens and protecting the plant health (Ramos‐Solano et al , ).…”
Section: Discussionsupporting
confidence: 90%
“…This low value may be due to synergistic action of different isoforms present in the crude supernatant and the loss of chitinase activity during the purification process. Those chitinases had a size range of 40-88 kDa which was typically larger than the sizes of plant (25-40 kDa) and bacterial (20-60 kDa) chitinases [13,16,17]. It has been also reported that the optimum temperature of insect chitinases ranged from 20 to 60°C toward different substrates such as colloidal chitin, GlcNAc 5 and glycol chitin [5,10,16].…”
Section: Discussionmentioning
confidence: 96%
“…Culture supernatant of Bacillus thuringiensis (Bt; strain BUPM255) was reported to have high antifungal activity against Aspergillus niger [11]. Further, the chitinases from two fungal strains can degrade the cell walls of Fusarium solani and also inhibit microconidial germination in this species [17]. Chitinases are also potentially useful as food preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin is the major structural component of various organisms, including fungi, insects, and crustaceans (Chernin et al, 1998). Chitinase is an enzyme that functions as a protective component of some bacteria in fighting against fungal or other pathogens with chitinous exoskeleton (Neiendam Nielsen & Sorensen, 1999;Nguyen et al, 2008). In C. violaceum, chitinase production was regulated by QS and upregulated by antibiotics, indicating that the antibiotics at SICs contribute to the success of C. violaceum in its competition with other inhabitants by improving QS-regulated behaviors.…”
Section: Discussionmentioning
confidence: 99%